The concept of total knowledge and its achievement Controversies in the fundamentalist front thesis - Salman Kadum Sadkhan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The research aims to find out whether or not total knowledge is feasible for jurists, as a serious attempt to bridge or reduce the knowledge gap in explaining the nature of the relationship between these variables, by exploring the opinions of the targeted sample, as the current research relied on the inductive, analytical and comparative approach. In the researcher’s quest to achieve the importance of the study by knowing what the jurists differed in, that total knowledge is like detailed knowledge by assignment. One of the most important of them is that general knowledge is not a detailed knowledge of the comprehensive without its application, unlike detailed knowledge, which is knowledge of the general application.